IDENTIFIKASI ZONA PROSPEK RESERVOAR BERDASARKAN DATA SEISMIK PADA LAPANGAN BOONSVILLE FORT WORTH BASIN TEXAS UNITED STATES OF AMERICA - Musyaffa, Nur Rafif; Mandang, Idris; Rahmiati, Rahmiati (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2021)
The aim of the research is to identify reservoir prospect zone in Caddo and Vineyard zone at Boonsville field, Fort Worth Basin, Texas, United States of America. In this research used 3D PSTM (Post Stack Time Migration) reflection seismic data and BY18D borehole data. Data processing of seismic inversion obtained Acoustic Impedance (AI) value. Well logging data obtained effective porosity (PHIE) value. From analysis, the results of reservoir zonation obtained on Caddo and Vineyard zone. Distribution of reservoir prospect zone in BY18D can be seen from depth marker data in 4735-5740 feet depth. After zonation process was conducted, effective porosity value (PHIE) was obtained. Analysis from well logging In Caddo zone, 12% porosity value obtained in 4735-4830 feet depth. In Vineyard zone, 13% porosity value obtained in 5647-5740 feet depth. The Results of the study is obtained effective porosity (PHIE) with moderate value. Afterward, in seismic inversion data processing, range of Acoustic Impedance value was obtained. In Caddo zone, the range is 37500-42500 (m/s)*(gr/cc). In Vineyard zone, the range is 35000-42500(m/s)*(gr/cc). The results describe high value of acoustic impedance seismic analysis results, it shows the high acoustic impedance value distribution, that indicated a moderate effective porosity (PHIE) value distribution.